2009
DOI: 10.2478/s11536-009-0021-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of L-carnitine against cisplatin-induced liver and kidney oxidant injury in rats

Abstract: AbstractThe present study was designed to investigate the protective effects of L-carnitine (LC) on changes in the levels of lipid peroxidation and endogenous antioxidants induced by cisplatin (cis-diamminedichloroplatinum II, CDDP) in the liver and kidney tissues of rats. Twenty-four Sprague Dawley rats were equally divided into four groups of six rats each: control, cisplatin, L-carnitine, and L-carnitine plus cisplatin. The degree of protection produced by L-carnitine was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…Endogenous L-carnitine is synthesized from lysine and methi- onine primarily in the liver, as well as in the kidneys and brain tissue [24]. Previous studies have indicated that L-carnitine has an important role in oxidative/antioxidative balance as well as in the transport function of long-chain fatty acids into the mitochondria in biological systems [12][13][14][15]. However, the effects of L-carnitine on specific antioxidant enzymes, such as GPX, CAT and MPO, which detoxify H 2 O 2 in water, have been reported independently in a few studies [14,25].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Endogenous L-carnitine is synthesized from lysine and methi- onine primarily in the liver, as well as in the kidneys and brain tissue [24]. Previous studies have indicated that L-carnitine has an important role in oxidative/antioxidative balance as well as in the transport function of long-chain fatty acids into the mitochondria in biological systems [12][13][14][15]. However, the effects of L-carnitine on specific antioxidant enzymes, such as GPX, CAT and MPO, which detoxify H 2 O 2 in water, have been reported independently in a few studies [14,25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that L-carnitine has an important role in oxidative/antioxidative balance as well as in the transport function of long-chain fatty acids into the mitochondria in biological systems [12][13][14][15]. However, the effects of L-carnitine on specific antioxidant enzymes, such as GPX, CAT and MPO, which detoxify H 2 O 2 in water, have been reported independently in a few studies [14,25]. There are no studies about the dose-dependent protective effect of L-carnitine against the free radical damage induced by hyperthyroidism in rat liver tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations